Biliary stone disease in patients receiving somatostatin analogs for neuroendocrine neoplasms. A retrospective observational study. Issue 5 (May 2019) - Brighi, Nicole; Lamberti, Giuseppe; Maggio, Ilaria; Manuzzi, Lisa; Ricci, Claudio; Casadei, Riccardo; Santini, Donatella; Mosconi, Cristina; Lisotti, Andrea; Ambrosini, Valentina; Pantaleo, Maria Abbondanza; Campana, Davide
Abstract: Background: Somatostatin analogs are the backbone of neuroendocrine neoplasms treatment. Biliary stone disease is a potentially severe adverse event of somatostatin analogs: an increased incidence has been reported in somatostatin analogs-treated acromegalic patients, but studies on patients with neuroendocrine neoplasms are lacking. Aims: To evaluate biliary stone disease incidence and associated factors in a large series of patients treated with somatostatin analogs for neuroendocrine neoplasms. Methods: A prospectively-collected database of patients with a diagnosis of neuroendocrine neoplasms of any grade and site, treated with somatostatin analogs at our Institution between 1995 and 2017, was retrospectively analyzed. Patients' demographics and disease characteristics were analyzed to evaluate the incidence and the factors related to biliary stone disease. Results: Three-hundred patients were included; 101 (33.7%) patients underwent cholecystectomy before starting somatostatin analogs. Among 164 patients with gallbladder in situ and no history of stone disease, 60 (36.6%) developed gallstones after a mean of 36.7 months (range 1–239) from treatment start with a mean yearly incidence of 8.73%. Previous cholecystectomy was associated with a lower rate of development of gallstones (p < 0.001) or related complications (p = 0.017). Conclusion: We observed a high incidence of biliary stone disease in patients treated with somatostatin analogs-treated for neuroendocrine neoplams. Previous cholecystectomy was the only factor associated with a lower occurrence of biliary stone disease.